Roo: A framework for real-time threads. - CAHILL, VINNY (IEEE Computer Society Press, 1995)
Traditional object-oriented real-time systems are often limited an that they provide only one approach to real-time object support. Taking the increasing demand for flexible and extensible object support environments into account, we discuss the design and implementation of a small object-oriented real-time executive based on a sub-framework which we call Roo. Roo is a component of the Tigger framework (our proposal for an extensible object support operating system) and is intended to support different object models providing soft real-time behaviour. Roo provides support for different mechanisms and policies for real-time thread management, scheduling and synchronization. In this it serves as a basis for other components of the Tigger framework
Proceedings of the 3rd Workshop on Parallel and Distributed Real-Time Systems
3rd Workshop on Parallel and Distributed Real-Time Systems
PUBLISHED
Santa Barbara, CA
Keywords: Computer Science